2016
DOI: 10.1111/sode.12203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pet Dogs on Children's Perceived Stress and Cortisol Stress Response

Abstract: The present study tested whether pet dogs have stress-buffering effects for children during a validated laboratory-based protocol, the Trier Social Stress Test for Children (TSST-C). Participants were 101 children aged 7–12 years with their primary caregivers and pet dogs. Children were randomly assigned in the TSST-C to a pet present condition or one of two comparison conditions: parent present or no support figure present. Baseline, response, and recovery indices of perceived stress and cortisol levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 75 publications
(98 reference statements)
2
61
0
3
Order By: Relevance
“…The sample size was relatively large for this type of research. The study, like Kertes et al (2016), is also unique in the child literature in focusing on the potential benefits of pets rather than service animals. We included multiple measures of emotional responding, as well as examining interaction between the child and his or her pet dog.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample size was relatively large for this type of research. The study, like Kertes et al (2016), is also unique in the child literature in focusing on the potential benefits of pets rather than service animals. We included multiple measures of emotional responding, as well as examining interaction between the child and his or her pet dog.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used small samples (15-20 children in a group; e.g., Beetz et al, 2011;Krause-Parello & Friedmann, 2014;Tsai et al, 2010) and thus had limited power, or used specialized samples (e.g., hospitalized children; Kaminski et al, 2002;Tsai et al, 2010) or settings (e.g., child visit to a doctor; e.g., Hansen et al, 1999;Havener et al, 2001;Nagengast et al, 1997) which limits their generalizability. Although it might be expected that the positive impact of human animal interaction might be greatest when children have an ongoing relationships with the animal (e.g., is a family pet), as has been found in studies with adults (Beetz et al, 2012), the prior studies we found with children that examined the impact of human animal interaction on emotional adaptation used trained unfamiliar animals rather than family pets (for a recent exception, see Kertes et al, 2016). Moreover, most studies have not controlled for whether children have prior experience with pets, a factor that might moderate the impact of human animal interaction.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…These reviews confirm that the task reliably induces several indices of responses to social stress, and they identify several variables that can influence TSST responses, including, for example, sex, menstrual cycle phase and hormones, age, genotype, time of day of testing, psychiatric diagnosis, symptomatic state (Zorn et al, 2017) and even the presence of a pet dog (e.g., Kertes et al, 2017). The fact that many variables can influence the stress response somewhat complicates the interpretation of pharmacological challenge studies with the TSST (referred to here as ph-TSST), because the drugs could affect the perception or impact of the stress indirectly, by influencing other variables.…”
Section: Introductionmentioning
confidence: 81%